Interdisciplinary approach to the management of medical supplies in the nursing home setting - Juan Francisco Peris Martí; Marta Monleón Ruiz; Antonio Montero Bau; Mónica Tomás Madrid; Ana Moreno Miralles; Isabel Quintana Vargas (Elsevier, 2017)
Introduction: Given the impact of pressure ulcers in institutionalized elderly people, an interdisciplinary approach to the care of ulcers and the management of medical supplies is essential. The aim of this study is to describe and evaluate the management of medical supplies by an interdisciplinary team in order to promote their rational use in the nursing home setting. Methods: An interdisciplinary team was set up, coordinated by a Pharmacy Unit including representatives of 18 elderly nursing homes (1,599 beds). Team interventions were assessed in terms of improvements in the management of wound care supplies. In addition, a retrospective descriptive study was carried out on those patients with pressure ulcers, in order to consider future interventions. Results: The team interventions led to a selection of 15% of the 180 wound care supplies from the public tender process. The monthly savings in wound dressing material purchases was at least 17%. Furthermore, a reduction in consumption greater than 50% was found in 7 centres. The prevalence of ulcers was 5.59%. A fourth of these ulcers were originated outside nursing homes. Conclusions: The creation of an interdisciplinary team, in which the pharmacist gets closer to patient needs, and where nurses share responsibility for the selection and management of medical supplies, leads to positive results and represents an opportunity for improvement in elderly care.